2006
DOI: 10.1152/ajpgi.00099.2006
|View full text |Cite
|
Sign up to set email alerts
|

A vH+-ATPase is present in cultured sheep ruminal epithelial cells

Abstract: Etschmann, Benjamin, Katrin Sophie Heipertz, Annabelle von der Schulenburg, and Monika Schweigel. A vH ϩ -ATPase is present in cultured sheep ruminal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Then, NHE2 and other NHE maintain intracellular pH through H 1 export as the cytosol becomes acidified by SCFA uptake. In support of this hypothesis, Etschmann et al (2006) demonstrated that NHE1 and NHE3 are the predominant isoforms expressed in cultured primary rumen epithelial cells, with expression of NHE2 being considerably lower, as determined by realtime qRT-PCR. The authors demonstrated through the use of specific inhibitors that NHE1 and NHE3 are responsible for 50% and 20% of the export of H 1 from epithelial cells, respectively, in the absence of HCO 3 2 and work in concert with other transporters described below in the maintenance of intracellular pH.…”
Section: Maintenance Of Rumen Phmentioning
confidence: 58%
See 2 more Smart Citations
“…Then, NHE2 and other NHE maintain intracellular pH through H 1 export as the cytosol becomes acidified by SCFA uptake. In support of this hypothesis, Etschmann et al (2006) demonstrated that NHE1 and NHE3 are the predominant isoforms expressed in cultured primary rumen epithelial cells, with expression of NHE2 being considerably lower, as determined by realtime qRT-PCR. The authors demonstrated through the use of specific inhibitors that NHE1 and NHE3 are responsible for 50% and 20% of the export of H 1 from epithelial cells, respectively, in the absence of HCO 3 2 and work in concert with other transporters described below in the maintenance of intracellular pH.…”
Section: Maintenance Of Rumen Phmentioning
confidence: 58%
“…Recent in vitro studies of primary ovine rumen epithelial cells showed that the vH 1 -ATPase contributes to approximately 30% of H 1 extrusion (Etschmann et al, 2006) for maintenance of intracellular pH in the absence of HCO 3 2 . Expression of vH 1 -ATPase mRNA was detected by RT-PCR in both isolated ovine and bovine rumen epithelial cells, as well as whole rumen epithelium collected at slaughter (Etschmann et al, 2006;Albrecht et al, 2008).…”
Section: Maintenance Of Rumen Phmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the protein involved in sodium-proton exchange (NHE) in ruminal epithelium is well documented (2,22,27,31,74), and SCFA are known to stimulate this pH-regulating transport protein in the rumen (25,76). If urea transport is mediated by changes in cytosolic pH, inhibition of NHE should lead to measurable effects.…”
Section: Effect Of Amiloride On Urea Flux At Ph 74mentioning
confidence: 99%
“…In addition to the Na ϩ /K ϩ -ATPase, the existence of functional vacuolar-type H ϩ -ATPases (vH ϩ -ATPase) in REC has been shown by our group (1,9). The vH ϩ -ATPase is a multisubunit enzyme complex composed of the V 1 sector (subunits A to H) responsible for the ATPase activity, and the membrane inserted V o sector (with at least subunits a to e), which functions in H ϩ translocation across limiting membranes (51).…”
mentioning
confidence: 91%